Mechanical Reliability of Power Electronic Systems - Schriefer, Thomas; Hofmann, Maximilian (9th International Conference on Integrated Power Electronics Systems, 2016)
The increasing integration of power electronic systems in highly stressed spaces to reduce interfaces, e.g. in the wheel hub or near the gearbox, leads to high demands for implemented electrical and mechanical components. To ensure field reliability new approaches predicting lifetime already in the development phase are necessary. The paper describes and applies a tool chain combining analytical, numerical and experimental methods to estimate the design life of an “Inverter Building Block” in a high-vibration environment. First, analytical models of bending beam and vibration theory are derived to pre-estimate its dynamic behavior. Second, a numerical model based on the finite element method is experimentally verified and power spectral density analysis applying standard loads are conducted. Third, a lifetime model referring to the linear damage accumulation thesis is implemented and compares the effects of different mounting scenarios in a passenger vehicle on the expected lifetime.<br
Keywords: Power electronics; Reliability; Vibration; Power Spectral Density; Lifetime